The Influence of Industrial Work Practice Experience on Entrepreneurial Interest in Students of Automotive Mechanical Engineering Expertise Program SMK Texmaco Pemalang - Rachmadiani, Sagita; Meliyani, Tania Dewi; Romansyah, Robby; Prastyo, Yudi; Wiyatno, Tri Ngudi (Engineering And Technology Journal, 2024)
Prakerin or Industrial Work Practice is an educational, training, and learning activity for Vocational High School (SMK) students conducted in the business world or the industrial world related to student competence in accordance with the field mastered. The purpose of this study is to determine whether there is an effect of work experience in the industry (Prakerin) on interest in entrepreneurship and how much influence. The subjects of this study include only class students. Where there are 88 students (2 classes), of which 44 students are used as a test and 44 other students as a research sample.